Demolishing the “Ideal” Concept of Beauty: How Pore Hero’s Instagram Campaign Challenges Other Skincare Advertisements - Yasmina Namira Rahmania; Nurenzia Yannuar; Aulia Apriana (PAROLE: Journal of Linguistics and Education, 2021)
Skincare companies purposely combine textual and visual features to create a compelling sign that can be correlated with beauty. In their ads, people are frequently depicted as having bright, white, and flawless skin. These exaggerated and repetitive representations eventually built a certain concept of beauty. In this paper, a preparatory approach is employed to investigate how an Indonesian beauty brand, Pore Hero, employs diverse promotional strategies. The analysis focuses on the textual aspects and discursive features of the posts, and how the campaign challenges the “ideological” concept of beauty. Data were collected from the brand’s Instagram account then analyzed with Fairclough’s three-dimensional model (1989) and van Leeuwen’s word-image links (2005b). Results indicated that Pore Hero uses five distinctive techniques to promote the brand’s values and offerings: 1) exposition of existing ingredients 2) inspiring campaign 3) emotive contents 4) realistic representations 5) reviews by Instagram users. It is concluded that the Instagram promotional posts of the brand strive to change people's minds to respect and accept themselves by changing the goal of having perfect skin to healthy skin.